Equal bequests and parental altruism: Compatibility or orthogonality? - Oded Stark (Institute for Advanced Studies (IHS), 1998)
The large amount of equal division of bequests by parents who otherwise would have compensated the earning differences among their children is attributed to the cost associated with unequal bequests. This paper identifies a source of this cost and explains why equal bequests to children whose earnings differ, and parental altruism toward these children, are not mutually exclusive.
Keywords: D10; D31; D63; D64; 330; parental altruism; equal bequests